PECULIARITIES IN THE DEVELOPMENT OF CHRONIC CEREBROVASCULAR PATHOLOGY WITH ARTERIAL HYPOTENSION IN YOUNG PATIENTS - Mavludakhon Mirkhamzaevna Mamurova; Rushana Shukhrat kizi Zhobborova (Scholar Express Journals, 2022)
Chronic cerebrovascular diseases (CVDs) occupy the leading position among all pathologies of the nervous system leading to temporary or permanent disability. The main causes of CVD are arterial hypertension (AH), narrowing of the main arteries of the head, disorders of rheological and coagulation properties of blood, essential arterial hypotension (EAH), vertebral artery compression and some other causes [1,2,9]. The mechanisms of chronic cerebral ischemia eventually lead to the development of the clinical syndrome of discirculatory encephalopathy, manifested by subjective and objective signs of organic brain pathology. The modern socio-economic situation, increased neuropsychological stresses have led to the rejuvenation and widespread occurrence of CVD [5,7,8].
Keywords: Chronic cerebrovascular disease; arterial hypotension; young age; brain